Doxorubicin‐induced and trastuzumab‐induced cardiotoxicity in mice is not prevented by metoprolol. (2nd February 2021) - Nicol, Martin; Sadoune, Malha; Polidano, Evelyne; Launay, Jean Marie; Samuel, Jane Lise; Azibani, Feriel; Cohen‐Solal, Alain
Abstract: Aims: Our objectives were to validate a murine model of chronic cardiotoxicity induced by Doxorubicin (Dox) and Trastuzumab (Trast) and to test the potential cardio‐protective effect of metoprolol. Methods and results: Male C57Bl6 mice were intraperitoneally injected during 2 weeks with Dox (24 mg/kg) or saline, and then with Trast (10 mg/kg) or saline for two more weeks. Half of the mice received metoprolol (100 mg/kg). Cardiotoxicity was defined by a decline in left ventricular ejection fraction (LVEF) ≥ 10 points. At Day 42, Dox + Trast‐treated mice exhibited a 13‐points decline in LVEF (74 ± 2.6% vs. 87 ± 0.8% for control mice, P  < 0.001) and a severe cardiac atrophy (heart weight: 105 ± 2.7 mg vs. 119 ± 3.9 mg for control mice, P  < 0.01). This cardiac atrophy resulted from an excess of cardiac necrosis (assessed by plasma cardiac troponin I level: 3.2 ± 0.4 ng/L vs. 1.3 ± 0.06 ng/L for control mice, P  < 0.01), an increase in apoptosis (caspase 3 activity showing a six‐fold increase for Dox + Trast‐treated mice vs. controls, P  < 0.001), and cardiomyocyte atrophy (myocyte size: 0.67 ± 0.08 μm 2 vs. 1.36 ± 0.10 μm 2 for control mice, P  < 0.001). In addition, Dox + Trast‐treated mice were shown to have an increased cardiac oxidative stress (164 ± 14 dihydroethidine‐marked nuclei per area vs. 56 ± 9.5 for control mice, P  < 0.01) and increased cardiac fibrosis (the semi‐quantitative fibrosis score was three‐fold higher for Dox + Trast‐treated mice as compared with controls, P  < 0.01). Metoprolol was not able to prevent either the decrease in LVEF or the severe cardiac atrophy, the cardiac necrosis, and the cardiac remodelling induced by chemotherapies. Conclusion: A murine model of chronic cardiotoxicity induced by Dox and Trast was characterized by a decrease in cardiac function, a cardiac apoptosis and necrosis leading to cardiomyocyte atrophy. Metoprolol did not prevent this cardiotoxicity.